Factors Affecting the Use of English in the Internal Communication Forum: A Case Study at an English Education Student Association of Universitas Majalengka - Zahrotun Nisa; Dina Windiarti; Eva Aviah Nur Azizah; Hilda Muthia Agustin; Eka Nurhidayat (Papanda Journal of English Education, 2024)
This research aimed to analyze the factors affecting the low use of English in the internal communication forum of the English Education Student Association of Universitas Majalengka members. This research has the problem of the lack of use of English in internal communication among English Education Student Association of Universitas Majalengka members as its background. Although they are the leading pioneers in the organization of language study programs, their communication still needs to improve in English, and Indonesian is more dominant in their use. This research uses qualitative methods, a case study approach with observation instruments, and semi-structured interviews. The researcher found that members of the English language association still do not use English in communication and discussion forums due to several factors, such as lack of vocabulary, confidence, worry about being wrong, and more comfortable discussing in Indonesian. Even so, the researcher suggested that association members use English more in their discussion forums to become the first step towards being good role models in their study program environment.